ANALISIS KEMAMPUAN PENALARAN MATEMATIS MAHASISWA PADA MATA KULIAH STRUKTUR ALJABAR - Masril Aguswandi Tudjuka; Evi Novianty (STKIP Paris Barantai, 2022)
The course algebraic structure is one of the compulsory subjects in the mathematics Education Study Program. One of the topics discussed in the structure course is group theory. The group theory is one the course algebraic structure that introduces the concept of modern algebra. In studying, the students are required to have the ability to think logically and reason systematically because the course algebraic structure is full of definitions and theorems. This study aimed to describe the ability of students’ mathematical reasoning in solving group problems. The method used in this study is a qualitative approach. This research has been carried out in the Mathematics Education of Study Program at the STKIP Paris Barantai, March 2022. The results show that high-ability of students are declared capable of reasoning on all indicators of mathematical reasoning ability, namely analyze, generalize, synthesize and justify; students with moderate abilities are stated to be able to reason on the analyze and generalize indicators, while the students that low abilities are only able to reason on the analyze indicators. Key words: Analysis of reasoning ability; group Struktur Aljabar.